The Galactic center: a model for cosmic ray interactions in starburst galaxies?. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Yoast-Hull, T.; Gallagher, J. S.; Zweibel, E.
Abstract: The Galactic center contains strong magnetic fields, high radiation fields, and dense molecular gas, as is also the case in starburst galaxies. The close proximity of the Galactic center allows for more and better observations of the interstellar medium than for extragalactic sources making it an ideal place for testing models for cosmic ray interactions. We compare our semi-analytic model for cosmic ray interactions to published data for both the Galactic center and the starburst galaxy NGC 253. We present the predicted radio and γ-ray spectra and compare the results with published measurements. In this way we provide a quantitative basis for assessing the degree to which the Galactic center resembles a starburst system.